2022
DOI: 10.3389/fimmu.2022.901872
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology and artificial intelligence analysis highlights the pleiotropic effect of IVIg therapy in autoimmune diseases with a predominant role on B cells and complement system

Abstract: Intravenous immunoglobulin (IVIg) is used as treatment for several autoimmune and inflammatory conditions, but its specific mechanisms are not fully understood. Herein, we aimed to evaluate, using systems biology and artificial intelligence techniques, the differences in the pathophysiological pathways of autoimmune and inflammatory conditions that show diverse responses to IVIg treatment. We also intended to determine the targets of IVIg involved in the best treatment response of the evaluated diseases. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…First, the proteomics data obtained from spleen and plasma in mice suggested that IVIG treatment for ITP should primarily focus on modulating the differentiation of T cell lines, T-cell receptor binding, IL-17 signaling pathway, FcγRs mediated phagocytosis, cytokines, chemokines, etc. These findings were consistent with the work of Wang et al [45], Ding et al [46], and Segú-Vergés et al [47]. In addition, Wang et al reported that ITP samples exhibited higher counts of macrophages and Th cells compared to normal…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, the proteomics data obtained from spleen and plasma in mice suggested that IVIG treatment for ITP should primarily focus on modulating the differentiation of T cell lines, T-cell receptor binding, IL-17 signaling pathway, FcγRs mediated phagocytosis, cytokines, chemokines, etc. These findings were consistent with the work of Wang et al [45], Ding et al [46], and Segú-Vergés et al [47]. In addition, Wang et al reported that ITP samples exhibited higher counts of macrophages and Th cells compared to normal…”
Section: Discussionsupporting
confidence: 91%
“…Concerning complement activation, Cristina Segú-Vergés et al found that diseases with good therapeutic effect of IVIG were characterized by an imbalance of B cells and complements system, suggesting a close relationship between IVIG and complement system [47]. Increasing evidence indicates that complement inhibition is a key anti-inflammatory mechanism of IVIG.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, IVIg has been applied to treating ITP. Studies on the pharmacological mechanism of IVIg have indicated that IVIg inhibits Fc-mediated phagocytosis of antibody-coated platelets by the reticuloendothelial system to protect platelets, promotes the development or activation of regulatory T cells, and regulates B-cell function and survival 40 41…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the pathophysiology of a select disease, different MoAs may act in concert (15, 34), yet distinct mechanisms may prevail (Figure 1). Indeed, a recent analysis based on artificial intelligence supports the notion that IVIG exerts pleiotropic effects, while distinct pathways, such as involving B cells or complement, were found to be more relevant for specific disorders (35). The inherent pluripotency of polyclonal IVIG and SCIG preparations might explain their efficacy in a magnitude of autoimmune and inflammatory diseases despite their heterogenous pathogenetic background.…”
Section: Diversitythe Added Value Of Polyclonal Immunoglobulin Prepar...mentioning
confidence: 99%